Influence of sorghum flour on the rheological properties of semi-finished wheat product - V. A. Bukhovets; O. B. Kamenewa; O. V. Kartavenko; K. A. Kuklina (Новые технологии)
Rheological processes are associated with irreversible residual deformations and flow of various plastic and viscous materials, stress and relaxation phenomena. In the food industry ingredients, semi-finished products and finished products have different rheological properties. These properties depend on various factors: substance composition, humidity, temperature, intensity and duration of thermal and mechanical effects. Study and application of various combinations of such effects in production can provide a given level of rheological characteristics throughout the entire technological process, which will stabilize product quality, increase yield and obtain finished products of constant, specified quality.The purpose of the research was to study the rheological properties of semi-finished products from a composite mixture of wheat and sorghum flour.The objects of the research were samples of semi-finished products containing 10, 20, 30, 40% of sorghum flour. The control sample contained 100% wheat flour of the highest grade.Mixolab device was used during testing to determine the water absorption capacity of the composite mixture, the rheological properties of the dough during kneading and heating. The state of the proteinproteinase (at temperatures from +20 to +50°C) and carbohydrate-amylase (at temperatures from +60 to +90°C) complexes of the baking mixture was studied on one sample of the sem-finished product.It was found that samples containing sorghum flour had a more stable dough, compared with the control sample, that was indicated by an increase in the dough stability time from 10,93 to 11,62 minutes. Also, with an increase in the amount of sorghum flour in the baking mixture from 10 to 30%, the starch retrogradation index decreased to 4,99 H*m in comparison with the control one – 5,71 H*m, which indicated an increase in the freshness time of the finished product.The results of the research can be used to create recipes for new products; development of technologies for the production of bakery, flour confectionery products; determination and quality control of finished products and semi-finished products.